Dampak Sumber Daya Manusia, Skala Usaha, Umur Usaha dan Pelatihan Akuntansi Terhadap Penggunaan Informasi Akuntansi pada UMKM - Mayla Khoiriyah; Vera Oktari (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2021)
To reduce problems that become obstacles to the development and growth of MSMEs such as limited capital, difficulties in raw materials, technological stuttering, low quality human resources and ineffective marketing methods can be overcome by applying and using accounting information. This study aims to determine the effect of human resources, business scale, business age and accounting training on the use of accounting information at MSMEs. This research used primary data with questionnaires as instruments. The method used for sample selection is purposive sampling. Samples obtained in this study were 120 MSMEs. But only 92 (76.67%) questionnaires were returned and could be processed. Data analysis technique used in this research is multiple linear regression. The results shows that human resources, business scale and accounting training affect the use of accounting information at MSMEs. While the age of the business does not affect the use of accounting information at MSMEs.